2023
DOI: 10.1002/htj.22959
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of ecofriendly R1234ze(E) refrigerant in an automotive air conditioning system

Yogendra V. Kuwar

Abstract: A mathematical model for an air conditioning system used in five‐seater cars is developed with R1234ze(E) and R134a refrigerants, consisting of real system geometry like an evaporator, compressor, condenser, and thermostatic expansion valve. The mathematical model includes refrigerant properties, heat transfer, and pressure loss correlations for two‐phase and single‐phase regions. The performance parameters of a system like evaporator cooling duty, condenser heat loss, compressor power, refrigerant flow rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the recent years, it has been observed that the various pure refrigerants, such as R436a, R515a, R456a, and R445a, as well as mixtures of R290 and R600a, and combinations like R1234yf with R134a and R1234ze (E), have been considered as potential replacements for R134a in various applications. In our previous work, 33,34 the experiments and simulation work were performed to investigate the performance of automotive AC systems with low GWP refrigerants R1234yf and R1234ze (E). In this research work, the investigation is focused on assessing the impact of several critical factors, including compressor speed, condensing air velocity and temperature, the humidity of cooling space on the cooling capacity, the work of the compressor, and the COP of the VCR system of a small 5 seaters passenger car is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, it has been observed that the various pure refrigerants, such as R436a, R515a, R456a, and R445a, as well as mixtures of R290 and R600a, and combinations like R1234yf with R134a and R1234ze (E), have been considered as potential replacements for R134a in various applications. In our previous work, 33,34 the experiments and simulation work were performed to investigate the performance of automotive AC systems with low GWP refrigerants R1234yf and R1234ze (E). In this research work, the investigation is focused on assessing the impact of several critical factors, including compressor speed, condensing air velocity and temperature, the humidity of cooling space on the cooling capacity, the work of the compressor, and the COP of the VCR system of a small 5 seaters passenger car is discussed.…”
Section: Introductionmentioning
confidence: 99%